The Life of A Swiftie: How Taylor Swift Maintains Social Capital Through Her Relationship with Swifties - Christiana, Merry; Mendoza, Bernice Amanda (J-Lalite: Journal of English Studies, 2025)
Social capital, a key concept within cultural studies, is particularly significant in the digital age, where community is often built through mediated interactions. This study offers a comprehensive analysis of American pop star Taylor Swift’s strategies for maintaining her relationship with her fan base, the “Swifties,” through the theoretical lenses of Pierre Bourdieu’s and Robert Putnam’s social capital frameworks. While much scholarship has focused on Swift’s lyrical content or economic impact, this research addresses a critical gap by focusing on Swift’s interactions with her fans and how these interactions contribute to building and maintaining social capital. Adopting a qualitative content analysis methodology, the study conducts a close reading of social media resources. The findings identify three primary strategies: the narrative songwriting in her albums that fosters deep personal connection; her curated social media presence, which cultivates a sense of intimacy and direct access; and the large-scale, communal experience of the recently concluded “The Eras Tour.” The analysis reveals a strong alignment between these activities and the core principles of social networks (Bourdieu), as well as trust and reciprocity (Putnam). This research concludes that Swift’s enduring success is fundamentally linked to her ability to strategically nurture social capital, offering a valuable model for understanding celebrity-fan dynamics and community-building in contemporary culture.